PRMT1 loss sensitizes cells to PRMT5 inhibition. Issue 10 (27th March 2019) - Gao, Guozhen; Zhang, Liang; Villarreal, Oscar D; He, Wei; Su, Dan; Bedford, Ella; Moh, Phoebe; Shen, Jianjun; Shi, Xiaobing; Bedford, Mark T; Xu, Han
Abstract: PRMT5 is an arginine methyltransferase that accounts for the vast majority of the symmetric methylation in cells. PRMT5 exerts its function when complexed with MEP50/WDR77. This activity is often elevated in cancer cells and correlates with poor prognosis, making PRMT5 a therapeutic target. To investigate the PRMT5 signaling pathway and to identify genes whose loss-of-function sensitizes cancer cells to PRMT5 inhibition, we performed a CRISPR/Cas9 genetic screen in the presence of a PRMT5 inhibitor. We identified known components of the PRMT5 writer/reader pathway including PRMT5 itself, MEP50/WDR77, PPP4C, SMNDC1 and SRSF3. Interestingly, loss of PRMT1, the major asymmetric arginine methyltransferase, also sensitizes cells to PRMT5 inhibition. We investigated the interplay between PRMT5 and PRMT1, and found that combinatorial inhibitor treatment of small cell lung cancer and pancreatic cancer cell models have a synergistic effect. Furthermore, MTAP -deleted cells, which harbor an attenuated PRMT5–MEP50 signaling pathway, are generally more sensitive to PRMT1 inhibition. Together, these findings demonstrate that there is a degree of redundancy between the PRMT5 and PRMT1 pathways, even though these two enzymes deposit different types of arginine methylation marks. Targeting this redundancy provides a vulnerability for tumors carrying a co-deletion of MTAP and the adjacent CDKN2A tumor suppressor gene.